Rancang Bangun Alat Pemberi Pakan Ikan Otomatis Menggunakan Pewaktu - Bastaman Syah; Winarto Winarto; Imam Sofi'i (Jurusan Teknologi Pertanian, 2015)
Feed is an important factor in the process of aquaculture. In addition to the accuracy of the amount of feed given, the time of administration also plays an important role in the effectiveness of the use of feed. The objectives of this researh are to minimize errors feeding, both in terms of the amount of feed given and the time of administration is by designing the wake of a tool that can provide the right amount of feed and time. A feeder fish automatically designed using a timer 0f 4 pieces, consisting 1 piece timer used to set an eating schedule, and 3 pieces of each of the other is used to set a long life electric motor driving the blower, set the interval between the electric motor driving the blower with motor electric propulsion auger, and set long-life electric motor driving the auger. The test results show that the performance of the tool fish feed spreader tool can operate in three time feeding, morning, afternoon and evening. Dosage of feed within 30 seconds can remove fish feed pellets weighing 375.2 grams for medium and 233 for small pellets. Throw distance of 2.2 m and a width of 1.70 m for the distribution of pellets being as well as the distance of the throw of 2,25 m wide and 1,68 m for the distribution of small pellets.Â Keywords: spreader fish feed, timer, auotomatic